Tales of Tourism: Global changes and tourism discourse - Smed, Karina M. (Academic Quarter | Akademisk kvarter, 2011)
Tales of Tourism - Global Changes and tourism discourse by Karina Smedpresents us with what has been the dominant discourse of tourism, i.e. a discourse which has had its roots in the West's economic and cultural hegemony and the problem of the formation of identity from the dichotomy "self" and the "others". The author discusses to which extent tourism discourse is global as the reception of it has been different depending on the context. Moreover, she reflects on the impact upon this global narrative that the new economic world order will have. The new and emergent economies lead to a flow of tourists in the opposite direction: from China, India and Russia to western countries and worldwide and this will probably change the concept of tourism and our idea of identities.